Analysis The Influence of Retailing Mix Towards Consumer Purchase Decision at Kinibalu Swalayan in Pekanbaru - Feli Fahlevi; Jushermi '; Rio Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at Kinibalu Swalayan No. 3 in Pekanbarucity of Riau Province. The research objectives was to determine the variables retailing mix (product, price, location, promotion, service, and physical environment) influence simultaneously and partially. And to determine which variables are the most dominant influence towards purchase decision at Kinibalu Swalayan in Pekanbaru. To achieve these objectives the research carried out by using a sample of 115 respondent, with accidental sampling method. Methods of data analysis using simultaneously and partially test (multiple linear regression analysis with SPSS Windows version 17). Based on the results of hypothesis testing, it is found that the variables of retailing mix (product, price, location, promotion, service and physical environment), proved to have a significant influence towards consumer purchase decisions at Kinibalu Swalayan in Pekanbaru. Recommendations that authors propose is Kinibalu Swalayan should be able to improve services to consumers. By providing services to customers in any way concerned service at the time of the transaction, simplifying payments. Avoid long queues which will reduce customer satisfaction will make a visit to the Kinibalu Swalayan in pekanbaru.Keywords: Retailing Mix (product, price, location, promotion, service andphysical environmant), purchase decision.